GAMBARAN PENGETAHUAN IBU TENTANG KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) DPT-HIB DI PUSKESMAS ASAM-ASAM TAHUN 2021 - Chrisnawati Chrisnawati; Subarjo Subarjo; Sapariah Anggraini; Anastasia Maratning (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2022)
Background: Data about Post Immunization Events cases in the form of fever, swelling and red injection marks due to the DPT-Hib vaccine in the Tanah Laut Regency area as many as 219 cases and at the Asam-Asam Health Center as many as 47 cases. The impact of that will cause stigma or trauma from mothers to participate in the immunization program. Therefore, it is very important the role and knowledge of mothers to be able to manage and handle DPT-Hib Post Immunization Events that occur in children, so that the immunization program can be followed optimally to completion. Objective: To determine the Mother's Knowledge About Adverse Events Post Immunization of DPT-Hib at Asam-Asam Health Center in 2021. Methods: This study with quantitative methods, with descriptive design and approach cross sectional. The sample of this study were 76 mothers who have infants or toddlers who carry out DPT-Hib immunization activities in the working area of ​​the Asam-Asam Health Center, with the technique Total Sampling. Primary data collection using a questionnaire. Results: The results of the study regarding the Description of Mother's Knowledge about Adverse Events Post Immunization of DPT-Hib at the Asam-Asam Health Center were mostly included in the good category as many as 65 respondents (86%), while 8 respondents were in the sufficient category (10%) and 3 respondents. respondents are included in the less category (4%). Conclusion: The Education of mothers about Adverse Events Post Immunization it is very necessary for the successful implementation of giving vaccines of DPT-Hib to children. Keywords: Post Immunization Events, DPT-Hib Immunization, Mother's Knowledge.